2017
DOI: 10.1186/s12872-016-0457-2
|View full text |Cite
|
Sign up to set email alerts
|

Transradial versus transfemoral approach for coronary angiography and angioplasty – A prospective, randomized comparison

Abstract: BackgroundPCI has been done traditionally through transfemoral route. But now transradial and transbrachial routes are also coming up in practice. We compared transradial versus transfemoral routes for ease of operability, time for procedure, complications, and failure rates through a prospective study.MethodsFour hundred Patients admitted in department of cardiology for percutaneous interventions were enrolled in the study. 200 patients were assigned to each group randomly. A single team did all the procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 22 publications
4
31
1
2
Order By: Relevance
“…experience, particularly on issues like avoiding repeated punctures, selecting the proper catheters for cannulating coronary ostia, and manipulating them in the aorta. [2][3][4] Aside from the requirement for a certain time interval to complete the learning curve, radial artery spasm (RAS) constitutes a major drawback for choosing radial access as the default technique for the operators. 3,4 In association with these two factors, the risk of procedural failure in transradial interventions is higher as compared to transfemoral route.…”
mentioning
confidence: 99%
“…experience, particularly on issues like avoiding repeated punctures, selecting the proper catheters for cannulating coronary ostia, and manipulating them in the aorta. [2][3][4] Aside from the requirement for a certain time interval to complete the learning curve, radial artery spasm (RAS) constitutes a major drawback for choosing radial access as the default technique for the operators. 3,4 In association with these two factors, the risk of procedural failure in transradial interventions is higher as compared to transfemoral route.…”
mentioning
confidence: 99%
“…The benefit in reduction of MACE has been proven even in with ACS who undergo transradial access (23) Further advantages of transradial approach include immediate ambulation, reduced post-procedure nursing care, reduced hospital stay and related costs, and an overwhelming patient preference for transradial angiography (24)(25)(26)(27)(28) . Opponents of radial access have cited an associated learning curve (29) with adopting the transradial approach resulting in longer procedural time and increased radiation exposure (30,31). Higher-volume radial operators however exhibit shorter procedural and fluoroscopy times as their procedural experience increases (32).…”
Section: Resultsmentioning
confidence: 99%
“…14 Radial puncture for the vascular access is on the rise among the interventionists, and few studies have shown that it is associated with significantly lower complications. 15 Problem with radial access is difficult navigation into the carotid system.…”
Section: Complications Related To Vascular Accessmentioning
confidence: 99%